Upper and/or Lower Respiratory Tract Infection Caused by Human Metapneumovirus After Allogeneic Hematopoietic Stem Cell Transplantation - Piñana, Jose Luis; Tridello, Gloria; Xhaard, Aliénor; Wendel, Lotus; Montoro, Juan; Vazquez, Lourdes; Heras, Inmaculada; Ljungman, Per; Mikulska, Malgorzata; Salmenniemi, Urpu; Perez, Ariadna; Kröger, Nicolaus; et al. (The Journal of infectious diseases, 2024)
BACKGROUND: Human metapneumovirus (hMPV) epidemiology, clinical characteristics and risk factors for poor outcome after allogeneic stem cell transplantation (allo-HCT) remain a poorly investigated area. METHODS: This retrospective multicenter cohort study examined the epidemiology, clinical characteristics, and risk factors for poor outcomes associated with human metapneumovirus (hMPV) infections in recipients of allo-HCT. RESULTS: We included 428 allo-HCT recipients who developed 438 hMPV infection episodes between January 2012 and January 2019. Most recipients were adults (93%). hMPV infections were diagnosed at a median of 373 days after allo-HCT. The infections were categorized as upper respiratory tract disease (URTD) or lower respiratory tract disease (LRTD), with 60% and 40% of cases, respectively. Patients with hMPV LRTD experienced the infection earlier in the transplant course and had higher rates of lymphopenia, neutropenia, corticosteroid use, and ribavirin therapy. Multivariate analysis identified lymphopenia and corticosteroid use (>30 mg/d) as independent risk factors for LRTD occurrence. The overall mortality at day 30 after hMPV detection was 2% for URTD, 12% for possible LRTD, and 21% for proven LRTD. Lymphopenia was the only independent risk factor associated with day 30 mortality in LRTD cases. CONCLUSIONS: These findings highlight the significance of lymphopenia and corticosteroid use in the development and severity of hMPV infections after allo-HCT, with lymphopenia being a predictor of higher mortality in LRTD cases.
Keywords: Hematopoietic Stem Cell Transplantation; retrospektivní studie; transplantace hematopoetických kmenových buněk; Humans; lidé; Retrospective Studies; Respiratory Tract Infections; Adult; Adrenal Cortex Hormones; Paramyxoviridae Infections; lymfopenie; Metapneumovirus; Cohort Studies; Lymphopenia; dospělí; hormony kůry nadledvin; kohortové studie; infekce dýchací soustavy; infekce viry z čeledi Paramyxoviridae